The Determinants of Real Earnings Management - Nia Yuniarsih; Anita Permatasari (Universitas Dinamika, 2022)
This study aims to define and analyse the relationship between firm size, profitability and real earnings management real earnings management is measured by Cohen et al dan Roychowdhury. Secondary data sources are used, namely, companies listed on the Indonesian Stock Exchange. Purposive sampling techniques are employed, with a new sample of observational data from the manufacturing company for the period 2019-2021. The results indicate that firm size, financial distress, and profitability positively affect real earnings management.